2017
DOI: 10.1016/j.cell.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular and Synaptic Architecture of the Mechanosensory Dorsal Horn

Abstract: SummaryThe deep dorsal horn is a poorly characterized spinal cord region implicated in processing low-threshold mechanoreceptor (LTMR) information. We report an array of mouse genetic tools for defining neuronal components and functions of the dorsal horn LTMR-recipient zone (LTMR-RZ), a role for LTMR-RZ processing in tactile perception, and the basic logic of LTMR-RZ organization. We found an unexpectedly high degree of neuronal diversity in the LTMR-RZ: seven excitatory and four inhibitory subtypes of intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
471
4
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 333 publications
(515 citation statements)
references
References 58 publications
39
471
4
1
Order By: Relevance
“…Utilizing TH 2a-CreER ; R26 LSL-YFP (Ai3) mice (Abraira et al, 2017) and postnatal tamoxifen injection to achieve sparse genetic labeling of sympathetic neurons and their dendrites within the SCG (Figure S4A–B), we observed the presence of P-TrkA (Y785) puncta associated with sympathetic neuron dendrites at all examined postnatal (P) ages: P7, P14, P21, and P42–P56 (Figure 5A). We note that both the number of P-TrkA (Y785) puncta (Figure 5B) and the number of synapses (immunohistochemically defined as Homer1-VAChT double positive puncta) within dendrites increase between developmental (P14) and young adult (P42–P56) ages (Figures 5C, S4C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing TH 2a-CreER ; R26 LSL-YFP (Ai3) mice (Abraira et al, 2017) and postnatal tamoxifen injection to achieve sparse genetic labeling of sympathetic neurons and their dendrites within the SCG (Figure S4A–B), we observed the presence of P-TrkA (Y785) puncta associated with sympathetic neuron dendrites at all examined postnatal (P) ages: P7, P14, P21, and P42–P56 (Figure 5A). We note that both the number of P-TrkA (Y785) puncta (Figure 5B) and the number of synapses (immunohistochemically defined as Homer1-VAChT double positive puncta) within dendrites increase between developmental (P14) and young adult (P42–P56) ages (Figures 5C, S4C).…”
Section: Resultsmentioning
confidence: 99%
“…TrkA Flag/Flag mice (Sharma et al, 2010) were maintained homozygous on a mixed background. TH -2A-CreER (Abraira et al, 2017) heterozygous males were crossed to homozygous Rosa -CAG-LSL-EYFP-WPRE (Madisen et al, 2010) reporter mice and were genotyped for TH-2A-CreER using the following primer set which detect both mutant and wild- type alleles; TH-2A-CreER-1: CATGCCCATATCCAATCTCC, TH-2A-CreER-2: CTGGAGCGCATGCAGTAGTA, and TH-2A-CreER-3: ATGTTTAGCTGGCCCAAATG. Male and female mice were used for in vitro experiments and male mice were used for in vivo experiments.…”
Section: Extended Experimental Proceduresmentioning
confidence: 99%
“…The vibrotactile stimulation-induced medial lemniscus (ML) ascending pathway terminates in the nucleus gracilis, nucleus cuneatus, posterior lateral nucleus of the thalamus, and para-brachial nuclei (PV) 65,66. Further, some Aβ fibers, which are activated by vibrotactile stimulation, terminate in a deep layer of the dorsal horn to relay ascending information via the anterior spinothalamic (ST) pathway 67. A previous study reported that the ST ascending pathway targets not only the thalamus but also the caudal ventrolateral medulla (VLM), lateral PV, and periaqueductal gray matter (PAG) 68,69.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these populations of nociceptors, some recent studies have implicated low threshold mechanoreceptors (C-LTMRs) in mediating mechanical pain to normally non-noxious stimuli in conditions of injury and chronic pain [5456]. The C-LTMRs have been most studied within the skin.…”
Section: Initiation Of Pain Signals From the Bone And Jointmentioning
confidence: 99%